Overconfidence as a driver of entrepreneurial market entry decisions: a critical appraisal - Anne Chwolka; Matthias G. Raith (Review of Managerial Science, 2022)
In characterizing entrepreneurial behavior, researchers often regard nascent entrepreneurs entering risky markets as overconfident. In this paper, we challenge this prevailing view and show that a more differentiated consideration reveals the effects of overconfidence on market entry to be ambiguous if not irrelevant. In a first step, we emphasize the inconclusiveness of past empirical evidence. With a simple decision model, we show that "observed" overconfidence can also be interpreted as the outcome of fully rational behavior when acknowledging information available to and acquired by the entrepreneur. We criticize that empirical studies, which neglect individually available information, inductively propose overconfidence for observed behavior without substantiating it with appropriate data. Nevertheless, we do not generally deny overconfidence in decision making. Thus, in a second step, we explicitly postulate confidence biases of an intended rational decision maker. This enables us to analyze through which channels they may affect market entry. By considering over- and underconfidence in the entrepreneur's forecasting ability, we find that market entry may be affected positively, negatively, or not at all, thereby revealing the overall ambiguity of confidence biases in decision behavior. Finally, we show formally that, even if overconfidence increases the probability of market entry, this does not make it a characteristic feature of market entrants. Overall, our objective is to debunk the myth of the overconfident entrepreneur and to promote the more important role of information in entrepreneurial decision making.
Keywords: D80; D83; D84; L1; L26; M13; 650; Overconfidence; Overestimation; Rational behavior; Decision making; Uncertainty; Information system